Transnational Terrorism and the Internet - Do, Quy-Toan; Gomez-Parra, Nicolas; Rijkers, Bob (World Bank, Washington, DC, 2021)
Does the internet enable the recruitment of transnational terrorists Using geo-referenced population census data and personnel records from the Islamic State in Iraq and the Levant—a highly tech-savvy terrorist organization—this paper shows that internet access has facilitated the organization’s recruitment of foreign fighters from Tunisia. The positive association between internet access and Daesh recruitment is robust to controlling for a large set of observable and unobservable confounders as well as instrumenting internet access rates with the incidence of lightning strikes.